EFFICIENCY OF THE BANKS’ ACTIVITY IN CONDITIONS OF DIGITALIZATION - Khutorna, Myroslava; Kostogryz, Victoria (Socio-economic relations in the digital society, 2020)
The peculiarities of the functioning of banks in the conditions of digitalization are investigated and the directions of increase of efficiency of activity of banking institutions of Ukraine are substantiated. The types of bank efficiency are generalized. The evolution of digital banking in terms of penetration into the system of financial activity of customers is represented by three stages and it is justified that the highest point of development is the «digital brain», ie such a system of interaction between customer and bank online, when all financial information on income, expenses The client’s financial desires are systematized by appropriate software, which not only creates models of financial interaction client-bank, but pushes the client to certain financial decisions, manages his financial behavior to ensure the implementation of all his financial needs. The main advantages of the digital transformation of the banking business include: increasing the efficiency of the existing infrastructure; emergence of qualitatively new business models; increasing the efficiency of the banking business by increasing revenue or reducing costs in existing business models. A comparative analysis of the advantages and disadvantages of financial technologies in ensuring the efficiency of the bank. In order to increase the efficiency of the bank’s activities, the optimization of the institution’s internal processes should include: digital translation of more than 75% of the bank’s operations; creation of a messenger and a digital assistant on the basis of a mobile bank; launching a voice assistant and using chatbots to identify customer satisfaction with the quality of banking services; bringing online access to 100% of financial and non-financial services for small and micro businesses; introduction of biometric customer identification; training clients in new service technologies through messengers, banking and social networks; creation of a platform for automation of banking marketing in order to increase the effectiveness of the bank’s advertising campaigns, development of new channels for attracting and serving customers, ensuring the stability of the flow of customers.
Keywords: efficiency; effectiveness; banking efficiency; digitalization of bank activity; financial technologies